The french government and the new challenges of the coming back of french jihadists : balancing between punishment and de-radicalization - Hollander, Lea (Πανεπιστήμιο Πελοποννήσου, 2018)
The aim of this Thesis is to focus on how governments can react towards the coming back of the foreign fighters from Syria and Iraq, and the French case will illustrate one of the possible state’s behavior. Our central research question is stated as follows: What are the possible policies a state can implement in order to respond to the returnees crisis and to ensure its citizens’ security ? States are facing a new threat since the collapse of ISIS, the foreign fighters are starting to come back, and the authorities have to find quick solutions to face this challenge. Governments are choosing between hard and soft measures or, to put in other words, between punishment and rehabilitation. Obviously, states are trying to find a balance between these two approaches, in order to fight the roots of the problem, namely radicalization, to ensure the security of the state, and also to respond to the pressure of the public opinion.
Keywords: Terrorism; National security; Jihad; Foreign fighters; Jihad; Terrorism; De-radicalization; Rehabilitation